The Impact of Product Quality, Price, and Service Quality on Consumer Satisfaction of Infinix Users in South Tangerang City - Ifan Haryanto; Agus Sriyanto; Septiana mustika pratama (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the influence of product quality, price, and service quality on customer satisfaction at several Official Infinix Stores in South Tangerang City. The research sample amounted to 98 respondents, with data processing using the SPSS 20 statistical analysis program. The results of the study show that product quality, price, and service quality have a significant influence partially on customer satisfaction of Infinix users in South Tangerang. Good product quality enhances customer perception of value and trust, competitive prices strengthen purchasing decisions, while responsive and friendly service quality strengthens customer loyalty. These findings confirm that customer satisfaction is not only determined by product factors alone, but also by a combination of appropriate prices and quality service. Thus, the strategy of increasing customer satisfaction at the Infinix Official Store needs to be carried out holistically through improving product quality, setting proportional prices, and improving service quality. This research makes a practical contribution to retail management in formulating marketing policies that are oriented towards customer satisfaction, while strengthening Infinix's competitiveness in the increasingly competitive smartphone market.